Analysis of deep gas accumulation conditions of the Upper Paleozoic in the southern Huanghua Depression. Issue 1 (November 2020) - Yang, Runze; Zhao, Changyi; Zhao, Xianzheng; Liu, Haitao; Pu, Xiugang; Li, Hongjun; Li, Chuanming
Abstract: Influenced by sedimentary and tectonic factors, the accumulation conditions and models of Permian reservoirs in southern Huanghua Depression are unclear. Based on geochemical data of source rocks and petrophysical property data of reservoirs, by means of seismic interpretation, geochemical testing and profile analysis of typical reservoirs, the accumulation conditions are clarified, and the accumulation model is put forward. The study show that the intensity of secondary hydrocanbon generation is a favorable condition for the formation of gas field. The thrust structural traps in Huanghua Depression were mainly formed in the Indosinian, and anticline traps were mainly developed in the Yanshanian and Himalayan. Several source-reservoir-cap assemblages were developed inside the buried hill. Strong tectonic activity created good migration paths for natural gas, and the matching of trap formation, tectonic activity and hydrocarbon expulsion is the key factor of the accumulation of gas. On this basis, the typical gas accumulation pattern is established.